THЕ ROLЕ OF PROSЕ TRADITIONS IN YOUTH STORIЕS (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role of prose traditions in modern youth storytelling. The author shows how the system of composition, themes and images formed in the development of Uzbek literature continues in the works of today's young writers and receives new interpretations.